PARTISIPASI STAKEHOLDER DALAM PENANGANAN ANAK DI LEMBAGA KESEJAHTERAAN SOSIAL ANAK KOTA BANJARMASIN - Rio Sumardika (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Stakeholder participation is the participation of various stakeholders in the process of achieving goals which begins with the stages of planning, decision making, implementation, monitoring and evaluation. However, in handling children in LKSAs in the City of Banjarmasin, the role of stakeholders is still very weak. The rights of stakeholders to participate in handling children are not carried out in accordance with their roles. The purpose of this study is to describe the role of stakeholders in handling children in LKSA Banjarmasin City, and what inhibiting factors are the problems of stakeholder participation. This study uses qualitative methods with thematic data analysis techniques, with data sources coming from interviews and documentation with resource persons from the Social Service, LKSA Al-Ikhlas, LKSA Sentosa, children in LKSA, donors and the community in the LKSA environment. The results of this study indicate that the role of stakeholders related to handling children in LKSA is very weak. This is due to the low knowledge and awareness of each stakeholder to participate in the handling of children in LKSAs. Various obstacles and challenges in handling children in LKSA are faced by stakeholders, especially the Banjarmasin City Social Service as the leading sector. The low level of knowledge and awareness is the main trigger for handling children in LKSAs. There should be a special forum that bridges stakeholder participation, and there should also be education for stakeholders to participate in handling children in LKSAs, so that in the future there will be synergies to achieve common goals.